LMTK3 escapes tumour suppressor miRNAs via sequestration of DDX5. Issue 1 (1st March 2016) - Jacob, Jimmy; Favicchio, Rosy; Karimian, Negin; Mehrabi, Maryam; Harding, Victoria; Castellano, Leandro; Stebbing, Justin; Giamas, Georgios
Highlights: LMTK3 regulates a subset of miRNAs, including miR-34a, miR-196a-2 and miR-182. LMTK3 binds to DDX5 and to the pri-miRNA of these three mature miRNAs, thereby promoting their processing from pri-miRNAs to pre-miRNAs. miR-34a and miR-182 bind to the 3'UTR of LMTK3 and inhibit its expression at the post-transcriptional and translational level respectively. Ectopic expression of miR-34a and miR-182 in LMTK3-overexpressed cell lines (MCF7-LMTK3 and MDA-MB-231-LMTK3) inhibits breast cancer proliferation, invasion and migration. Abstract: Lemur tyrosine kinase-3 (LMTK3) plays an important role in cancer progression and is associated with breast, lung, gastric and colorectal cancer. MicroRNAs (miRNAs) are small endogenous non-coding RNAs that typically repress target genes at post-transcriptional level and have an important role in tumorigenesis. By performing a miRNA expression profile, we identified a subset of miRNAs modulated by LMTK3. We show that LMTK3 induces miR-34a, miR-196-a2 and miR-182 levels by interacting with DEAD-box RNA helicase p68 (DDX5). LMTK3 binds via DDX5 to the pri-miRNA of these three mature miRNAs, thereby sequestrating them from further processing. Ectopic expression of miR-34a and miR-182 in LMTK3-overexpressing cell lines (MCF7-LMTK3 and MDA-MB-231-LMTK3) inhibits breast cancer proliferation, invasion and migration. Interestingly, miR-34a and miR-182 directly bind to the 3'UTR of LMTK3 mRNA and consequently inhibit both its stability and translation, acting as tumour suppressor-like miRNAs. In aggregate, we show that LMTK3 is involved in miRNA biogenesis through modulation of the Microprocessor complex, inducing miRNAs that target LMTK3 itself.